2004
DOI: 10.1007/s10295-004-0184-z
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of a milk?soymilk and Lycium chinense Miller mixture using a new isolate of Lactobacillus paracasei subsp. paracasei NTU101 and Bifidobacterium longum

Abstract: A milk-soymilk mixture was fermented using Lactobacillus paracasei subsp. paracasei NTU101 and Bifidobacterium longum BCRC11847 at different inoculum ratios (1:1, 1:2, 1:5, 2:1, and 5:1). When the inoculum ratio was 1:2, the cell numbers of both strains were balanced after 12 h of cultivation. The pH and titratable acidity were very similar at the various inoculum ratios of cultivation. The milk-soymilk mixture was supplemented with 5, 10, 15, and 20% Lycium chinense Miller juice and fermented with Lactobacill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 36 publications
3
27
0
Order By: Relevance
“…The final pH values of our products ensure consumer acceptance (Hoogenkamp & Evers, 2011). Similar results are reported by Macedo, Renato, Freitas, Pandey, and Soccol (1999) and Lin, Chiu, and Pan (2004).…”
Section: Evaluation Of Products Characteristics During Cold Storagesupporting
confidence: 91%
See 1 more Smart Citation
“…The final pH values of our products ensure consumer acceptance (Hoogenkamp & Evers, 2011). Similar results are reported by Macedo, Renato, Freitas, Pandey, and Soccol (1999) and Lin, Chiu, and Pan (2004).…”
Section: Evaluation Of Products Characteristics During Cold Storagesupporting
confidence: 91%
“…Anyway, this decrease of WHC did not affect the stability of the fermented beverages as no obvious syneresis phenomenon was obtained during 14 days of storage at 48C. Lin et al (2004) reported that syneresis did not occur during storage of beverages based on milk, soy milk, and Lycium chinense Miller juice and fermented with Lactobacillus paracasei subsp. paracasei NTU101 and Bifidobacterium longum.…”
Section: Evaluation Of Products Characteristics During Cold Storagementioning
confidence: 94%
“…Soymilk is suitable for the growth of LAB and bifidobacteria [100,101]. Several studies have focused on developing fermented soymilk with different strains of LAB and Bifidobacteria to produce a soymilk product with improved health benefits [62,[101][102][103]. Soymilk is now known for their health benefits such as prevention of chronic diseases such as menopausal disorder, cancer, atherosclerosis, and osteoporosis, therefore, soymilk fermented with bifidobacteria may be a unique functional food [62,104].…”
Section: Vegetable-based Probiotic Productsmentioning
confidence: 99%
“…paracasei NTU 101 and L. plantarum NTU 102, two Taiwan-native strains of LAB isolated from human faeces and homemade Korean-style cabbage pickle, we found that both strains resist gastric juice and bile salts in the natural environment and show 'probiotic' characteristics that are effective in reducing cholesterol in the blood and liver (Chiu, Lu, Tseng, & Pan, 2006;Lin, Chiu, & Pan, 2004). In addition, NTU 102 enhances the cellular and humoral immune responses, such as phenol oxidase (PO) and superoxide dismutase (SOD) activities and clearance efficiency against Vibrio alginolyticus in Litopenaeus vannamei (Pacific white shrimp) (Chiu, Guu, Liu, Pan, & Cheng, 2007) and higher atherosclerosis-preventing activity of fermented milkÁsoymilk supplemented with Momordica charantia (Tsai, Chu, Lee, & Pan, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…paracasei NTU 101 and L. plantarum NTU 102, isolated from infant faecal and Korean-style cabbage pickles (Chiu et al, 2006;Lin et al, 2004), were stored at (808C refrigerator.…”
Section: Materials and Methods Strainsmentioning
confidence: 99%